Historical and Legal Preconditions for the Origin of Local Legal Regulation of Labor Legal Relations in Ukraine - V. V. Sychova (Bulletin of Kharkiv National University of Internal Affairs)
Based on the analysis of scientific views of scholars, the author has studied the historical and legal preconditions for the origin of local legal regulation of labor legal relations in Ukraine. It has been noted that the foundations of legal regulation of labor legal relations were laid during the existence of the Roman Empire. Despite the fact that this historical period is characterized by a slave-owning type of economy, we can still talk about the existence of legal regulation of labor at that time.